Does FDI and Corruption affect Environmental Quality in Tunisia? - Hfaiedh, Mohamed Ali; Bardi, Wajdi (International Journal of Energy Economics and Policy, 2021)
This paper investigates the impact of foreign direct investment (FDI) and corruption on the environmental pollution in Tunisia over the period 1984–2014 by applying an autoregressive distributed lag model. Our results revealed the existence of Environmental Kuznets Curve in Tunisian case. The pollution haven hypothesis postulates that polluting industrial activity in developed countries is shifting to developing countries with less stringent environmental regulations. This hypothesis has been proved. Hence, this study advises to make more aware to the negative effect of corruption. Overall, to improve environmental quality, the findings suggest that Tunisia should promote energy efficiency with sustainable growth. Therefore, results show that Tunisia should encourage more FDI inflows particularly in technology- intensive and environment-friendly industries. Keywords: FDI; economic growth; CO2 emission; corruption; EKC hypothesis, ARDL model. JEL Classifications: F21; O43 ; O13 ; C3 DOI: https://doi.org/10.32479/ijeep.11089